2013
DOI: 10.1007/s40484-014-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Generic properties of random gene regulatory networks

Abstract: Modeling gene regulatory networks (GRNs) is an important topic in systems biology. Although there has been much work focusing on various specific systems, the generic behavior of GRNs with continuous variables is still elusive. In particular, it is not clear typically how attractors partition among the three types of orbits: steady state, periodic and chaotic, and how the dynamical properties change with network’s topological characteristics. In this work, we first investigated these questions in random GRNs w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
(34 reference statements)
2
20
0
Order By: Relevance
“…3A) and we observed that about 20% of models allow two coexisting stable steady states (bi-stability), while the remainder allow only one steady state (mono-stability). The observation that only a small fraction of TS models work as a bi-stable system is consistent with a previous study [39].…”
Section: Racipe As An Unbiased Methods To Predict Robust Gene States Fsupporting
confidence: 92%
See 1 more Smart Citation
“…3A) and we observed that about 20% of models allow two coexisting stable steady states (bi-stability), while the remainder allow only one steady state (mono-stability). The observation that only a small fraction of TS models work as a bi-stable system is consistent with a previous study [39].…”
Section: Racipe As An Unbiased Methods To Predict Robust Gene States Fsupporting
confidence: 92%
“…From the in silico generated data, we apply statistical analysis to identify the most probable features within all of the models, a process which can uncover the most robust functions of the core circuit. It is worth-noting that RACIPE is unique in the way it utilizes perturbation and the integration of statistical tools, compared to the traditional parameter sensitivity analysis [34][35][36][37][38] and the previous studies on random circuit topology [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy has likewise been modeled as a chaotic disorder [101]. Much mathematical modeling has been done on gene networks that can give rise to chaos in both non-delayed [98,102,103] and delayed [82,104,105] In fact, none of the motifs analyzed so far can ever produce chaotic dynamics. This is because cyclic network topology (no more than one loop) and monotonic regulation guarantee that a system of delay equations will not have any chaotic solutions [42].…”
Section: Motif Vi: Double Feedbackmentioning
confidence: 99%
“…A total of 11 equations are used to describe the ageing network dynamics. We assumed that the regulatory interactions among ageing genes can be quantitatively modelled by the activations and repressions described by the sigmoid-shaped Hill function [29]. Variables x i and x j , respectively, represent the gene expression levels and the corresponding concentrations of gene production that activate or inhibit the expression of gene k. Parameter w k represents the relative strength of every regulation of gene k, which determines the maximum value of the corresponding Hill function.…”
Section: Model Network Wiring and Dynamicsmentioning
confidence: 99%